Development of a Sprayable Thermosensitive Hydrogel Containing Rambutan (Nephelium Lappaceum L) Leaf Extract for Diabetic Wound Therapy - Nisa’, Khairun; Zahro, Tarisha Elmaningtyas; Nurrohmah, Ayu Dini; Hanifah, Dini; Farid, Muhammad; Pertiwi, Deasy Vanda (Scripta Medica, 2026)
Background/Aim: Diabetic wounds are challenging to treat due to impaired healing processes. This study aimed to develop a sprayable thermosensitive hydrogel incorporating rambutan (Nephelium lappaceum L) leaf extract, known for its phytochemical wound healing potential. Methods: Rambutan leaves were extracted via 70 % ethanol maceration. Qualitative and quantitative analyses confirmed the presence of tannins and flavonoids. The extract was formulated into thermosensitive hydrogels (F1–F3) using sodium alginate, Poloxamer 407 and Poloxamer 188. Physical properties were evaluated and wound healing efficacy was tested on diabetic rats over 21 days using a full-thickness wound model. Results: The extract yielded 25.44 % with tannin and flavonoid contents of 2.94 % and 5.73 %, respectively. All formulations were homogeneous, pH-balanced (4.52–5.03) and met ideal criteria for spreadability, gelation, swelling and viscosity. In vivo tests showed F3 had the highest wound healing rate (81.25 %), approaching the normal control (84.00 %) and outperforming the reference drug (61.67 %). Statistical analysis indicated significant differences (p < 0.05). Conclusion: The thermosensitive hydrogel with rambutan leaf extract effectively accelerates diabetic wound healing and shows potential as a topical therapy.